Serial regression of primary gastric diffuse large B cell lymphoma after Helicobacter pylori eradication therapy: A case report - Ting‐Wei Lyu; Shan‐Chi Yu; Chien‐Chin Lin (Clinical Case Reports, 2024)
Key Clinical Message Primary gastric diffuse large B‐cell lymphoma (DLBCL), a rare malignancy linked to Helicobacter pylori (HP) infection, in this case regressed to low‐grade lymphoma and then achieved complete remission after HP eradication (HPE), highlighting this unique interim change and the potential of HPE as an effective treatment for early‐stage cases. Abstract Primary gastric diffuse large B‐cell lymphoma (DLBCL) is a rare malignancy. Like gastric mucosa‐associated lymphoid tissue (MALT) lymphoma, HP infection is implicated in lymphomagenesis and has thus emerged as a therapeutic target. Studies have demonstrated the sustained efficacy of HP eradication alone for limited‐stage primary gastric DLBCL. This report presents the case of a 53‐year‐old woman with stage IE gastric DLBCL who received triple therapy for HP eradication and experienced an interim histological transformation to MALT lymphoma, ultimately achieving complete pathologic remission. HP eradication therapy may represent a viable treatment option for patients with early‐stage primary gastric DLBCL.